2023
DOI: 10.1055/a-2015-8041
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End Products: Dementia and Cognitive Impairment

Abstract: The pathophysiological processes of dementia and cognitive impairment are linked to advanced glycation end products (AGEs) and their receptor (RAGE).The neurofibrillary tangles (NFTs) of abnormally hyperphosphorylated tau protein and senile plaques (SPs), which are brought on by amyloid beta (Aβ) deposition, are the hallmarks of Alzheimer’s disease (AD), a progressive neurodegenerative condition. Advanced glycat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Caspases 2 and 3 cleave the C-terminus at Asp314 and Asp421, respectively, while caspase 6 cleaves the N-terminus. In addition to affecting microtubule binding and aggregation, cleaving the C-terminal of tau has been linked to mitochondrial and synaptic damage [46][47][48][49][50]. However, it is important to note that not all post-translational modifications (PTMs) contribute to the acceleration of tau pathology and Alzheimer's disease (AD) progression.…”
Section: Pathological State Of Taumentioning
confidence: 99%
See 1 more Smart Citation
“…Caspases 2 and 3 cleave the C-terminus at Asp314 and Asp421, respectively, while caspase 6 cleaves the N-terminus. In addition to affecting microtubule binding and aggregation, cleaving the C-terminal of tau has been linked to mitochondrial and synaptic damage [46][47][48][49][50]. However, it is important to note that not all post-translational modifications (PTMs) contribute to the acceleration of tau pathology and Alzheimer's disease (AD) progression.…”
Section: Pathological State Of Taumentioning
confidence: 99%
“…Another tau PTM, dityrosine (DiY) cross-links, is induced by oxidative stress and has been observed on human AD-derived tau oligomers and PHFs. Interestingly, DiY cross-links can facilitate the formation of non-toxic, soluble tau oligomers, inhibit the formation of β-sheets and further extension of prefibrils, and increase the insolubility and stability of tau fibrils in AD [51][52][53][54].…”
Section: Pathological State Of Taumentioning
confidence: 99%
“…The oleogel formulation with a concentration of 4.5 % Na-CMC and 12.5 % beeswax, with the addition of AgNPs, resulted in a semi-solid preparation with the scent of coconut oil and a pH of 5, deemed safe for human skin application. [47] The test results for oil-binding capacity and spreading power were obtained at 99.83 % and 4.6 cm, respectively. Organoleptic and homogeneity tests indicated that the oleogel ointment preparation is homogeneous and stable, showing no changes in physical properties.…”
Section: Oleogel Characterizationmentioning
confidence: 99%
“…The main protein that stores iron is called ferritin, and brain iron levels may be reflected in CSF ferritin levels. In particular in individuals with high A-deposition or APOE-4 carriers, studies have indicated that CSF ferritin can be recognised as a possible biomarker, which is better to predict disease progression and future cognitive impairment [14]. Moreover, a high likelihood of brain hypometabolism and cognitive impairment is indicated by high CSF ferritin levels.…”
Section: Role Of Ferritin In Ad Pathology Mechanismmentioning
confidence: 99%